Exploring the benefits of multiple injections in low temperature combustion using a diesel surrogate model. (1st February 2016) - Anand, K.; Reitz, R.D.
Highlights: Surrogate composition of diesel fuel arrived by modeling its distillation profile. Surrogate model captured well LTC trends with EGR in single and multiple injections. Locations of UHC and CO emissions are different in single and multiple injections. Ignition delay to be optimized for lower combustion noise and unburned emissions in LTC. Abstract: Advanced low temperature combustion (LTC) strategies are promising to achieve high efficiency and low emissions of nitric oxides (NOx) and Particulate Matter (soot). The thermal efficiency advantages are obtained through lower temperatures with reduced heat losses. A lower charge temperature and the sufficiently longer time available for mixing help to avoid NOx and soot formation zones. However, important shortcomings of LTC strategies include higher unburned hydrocarbon emissions and higher combustion noise. The present work investigates the use of multiple injection strategies to combat the above shortcomings in low temperature diesel combustion. Numerical investigations were carried out using a three dimensional computational fluid dynamic (CFD) code KIVA-ERC-CHEMKIN to explore the benefits of multiple injections over a single injection. The physical and chemical properties of a typical American diesel fuel used in the present work were modeled using suitable surrogate components. The results show that significant benefits are possible with the use of multiple injections, including lower unburned emissions and lower combustion noise. The CFD investigations provide a better understanding of the mechanisms behind the benefits and are useful to suggest guidelines for further improvements.